624.BIONIC PRINCIPLES OF SPACE OPTIMIZATION APPLIED IN THE PRODUCT DESIGN PROCESS - Nikola, Gerasimovski; Elena, Angeleska; Sofija, Sidorenko (MECHANICAL ENGINEERING – SCIENTIFIC JOURNAL, 2020)
The main goal of the research presented in this paper is providing multi-functionality and space optimization of products by exploring and applying modern bionic and design principles. The specific design issue that needed to be addressed was – design of a multifunctional mountain hiking backpack that allows optimal use of space and maximal comfort when being used. An ideal solution to this stated problem was accomplished by following several phases in the process: study of available literature in the areas of multifunctionality, adaptability and product optimization; analysis of bionic phenomena which were the basic inspiration for creating a modular and compact design; detailed analysis of ergonomic aspects and anthropometric measurements; recognition of the target group and market analysis; materials analysis; development of design solutions and selection of the most suitable concept according to its strongest fulfillment of the given design requirements; elaboration of the final concept and its evaluation.